Brand Identity Nagari Pariangan, Desa Terindah di Dunia Kabupaten Tanah Datar, Sumatera Barat - Muhammad Syukri Erwin; Zainal Warhat; Syafwandi Syafwandi (Besaung : Jurnal Seni Desain dan Budaya, 2019)
ABSTRACTA city of  Pariangan is an old city in Minangkabau. A city called as the area of origin of the ancestors of the Minangkabau people that have a lot of potential both natural beauty and culture that is still exist and protected. Through the design of brand identity, the various potentials in the city of  Pariangan is  such a beautiful way that the creation of an effective promotional activities. So it can increase the number of tourists visiting both local and foreign. This will affect the economic sector of the community, either directly or indirectly. In the application of the concept that is inspired from the unique visual design  of Pariangan city.  Like the illumination motif of the ancient manuscript of Pariangan such as "Kambang Reno",  a pointed roof typically of Minangkabau, roof terraced from the old mosque  that became the pride of society and the typical stairs of Pariangan city. The color choice of yellow, brown and green to symbolize the natural cycles are some  process of planting to harvest the rice. A brand identity of Pariangan city are designed into logos and supporting media such as stationaries, sovenir and social media that synergize together into a visual unity. The Synergy between the media will affect the image formation of the Pariangan city itself to be easier to remember and recognizeable by tourists. The successfulness of this brand identity affects the cooperation of various parties to always be consistent to apply and use  this brand.Keywords: City of  Pariangan, brand identity, an old city, tourist areaABSTRAKNagari Pariangan adalah sebuah nagari tuo yang ada di Minangkabau. Nagari yang disebut sebagai daerah asal mulanya nenek moyang orang Minangkabau memiliki banyak potensi baik keelokan alam dan budayanya yang masih terjaga. Melalui perancangan brand identity, berbagai potensi yang ada di nagari Pariangan di kemas sedemikian rupa agar terciptanya sebuah kegiatan promosi yang efektif. Sehingga bisa meningkatkan jumlah wisatawan yang berkunjung baik lokal maupun mancanegara. Hal ini akan berpengaruh pada sektor ekonomi masyarakat baik langsung ataupun tidak langsung. Menggunakan konsep yang terinspirasi dari bentuk visual khas nagari Pariangan. Seperti motif iluminasi naskah kuno dari nagari Pariangan yaitunya “Kambang Reno”, bantuk gonjong khas Minangkabau, atap bertingkat dari surau tua yang menjadi kebanggaan masyarakat dan jenjang khas nagari Pariangan. Pemilihan warna kuning, coklat dan hijau untuk melambangkan siklus alam dari proses menanam hingga memanen padi. Perancangan brand identity nagari Pariangan meliputi logo dan media pendukung seperti stationari, sovenir dan sosial media yang saling bersinergi membentuk sebuah kesatuan visual. Sinergi antara media akan berpengaruh kepada pembentukan image terhadap nagari Pariangan agar mudah diingat, dikenali oleh wisatawan. Keberhasilan dari brand identitiy ini berpengaruh kepada kerjasama berbagai pihak untuk selalu konsisten menggunakan brand ini.Kata kunci : Nagari Pariangan, brand identity, Nagari tuo, kawasan wisata